Far Upstream Element-Binding Protein 1 Binds the 3′ Untranslated Region of PKD2 and Suppresses Its Translation - Zheng, Wang (J Am Soc Nephrol, 2016)
Autosomal dominant polycystic kidney disease pathogenesis can be recapitulated in animal models by gene mutations in or dosage alterations of polycystic kidney disease 1 (PKD1) or PKD2, demonstrating that too much and too little PKD1/PKD2 are both pathogenic. Gene dosage manipulation has become an appealing approach by which to compensate for loss or gain of gene function, but the mechanisms controlling PKD2 expression remain incompletely characterized. In this study, using cultured mammalian cells and dual-luciferase assays, we found that the 3′ untranslated region (3′UTR) of PKD2 mRNA inhibits luciferase protein expression. We then identified nucleotides 691–1044, which we called 3FI, as the 3′UTR fragment necessary for repressing the expression of luciferase or PKD2 in this system. Using a pull-down assay and mass spectrometry we identified far upstream element-binding protein 1 (FUBP1) as a 3FI-binding protein. In vitro overexpression of FUBP1 inhibited the expression of PKD2 protein but not mRNA. In embryonic zebrafish, FUBP1 knockdown (KD) by morpholino injection increased PKD2 expression and alleviated fish tail curling caused by morpholino-mediated KD of PKD2. Conversely, FUBP1 overexpression by mRNA injection significantly increased pronephric cyst occurrence and tail curling in zebrafish embryos. Furthermore, FUBP1 binds directly to eukaryotic translation initiation factor 4E-binding protein 1, indicating a link to the translation initiation complex. These results show that FUBP1 binds 3FI in the PKD2 3′UTR to inhibit PKD2 translation, regulating zebrafish disease phenotypes associated with PKD2 KD.